Project Management Practices- Case Studies At Food & Beverage Smes In Seberang Perai Municipality - Jamaludin, Lily (Universiti Sains Malaysia, 2017)
Small to medium-sized enterprises (SMEs) in food and beverage sector is developing and has become an indicator for economic specifically in matters of innovation, growth and employment. Project management is complimentary to the contribution but somehow SMEs does not need an advanced or modern project management for their organization. SMEs are more likely to practice less complex version of project management. This study is undertaken to identify the project management practices adopted by food and beverages SMEs in Seberang Perai Municipality, Pulau Pinang. Also, to recommend the project management practices that fits the nature of the company. The results of the three case study are reported in this paper. Managers and founders of the SMEs companies in food and beverage sector are being interviewed through a semi-structured interview. It is found that the companies adopt almost similar project management approaches in their organization for innovation, product development and growth. The style of project management is more to the laissez-faire and not as complex as project management used by large companies with large projects. The results identified project management practices within each of the case study namely Quality management, Customer Requirements, activity list in such activity vs due date and the target, informal human resource management, communication management, and scope and resource management. In particular, the project management practices are appropriate since their companies are micro-sized companies and they have small project teams to support the work of generalists. However, the directors also the managers or founders need to explore more about PMBOK to make project into success. This study will then will not only be beneficial to the companies it selves but also to the SMEs, food and beverage industry and customers. Apart from that, it is suggested that for further investigation of this research to include the critical success factors of project management and also focuses on particular project types